Où en est la situation de la violence envers les femmes dans le milieu familial, dix ans après les colloques sur la violence ? - Larouche, Ginette; Gagné, Louise (Criminologie, 1990)
The article presents the situation regarding violence to women for the region of Montreal. The nature and extent of the problem is examined and the risk factors are dealt with from a multidimensional point of view. The community and para-public services associated with this problem are described briefly and an account is given of the impact of past and present action. Some future prospects are also introduced.